ENGARUH OPINI AUDIT DAN FINANCIAL DISTRESS TERHADAP AUDIT DELAY PADA PERUSAHAAN SEKTOR PROPERTY DAN REAL ESTATE YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2020-2022 - Keumala, Adhenia; Hidayat, Taufik; Nurfai (Mulia Pratama, 2024)
The company's financial statements can be audited by a Public Accounting Firm to ensure their fairness and form of accountability to investors as well as demands from stakeholders and related authorities. Public Accounting Firms need time to complete their audit work, the time needed by public accounting firms to complete their audit work is called audit delay. There are factors that can affect audit delay. Based on agency theory, audit delays may be caused by a conflict of interest between company management and its shareholders. According to signal theory, audit delays can be used as a signal to investors and other stakeholders about the company's financial health. This study aims to determine the effect of audit opinion and financial distress on the time required to complete audit financial statements (audit delay). Audit opinion is an opinion given by an external auditor regarding the fairness of a company's financial statements. Financial distress is a condition where a company cannot fulfill its financial obligations to debtors. The research sample consisted of 68 property and real estate sector companies listed on the Indonesia Stock Exchange for three consecutive years during the period 2020-2022. This study es the multiple regression analysis method. The results of this study found that audit opinion has a significant negative effect on audit delay with a regression coefficient of -107.975. Financial distress has a significant positive effect on audit delay with a regression coefficient of 0.005. Audit opinion and financial distress simultaneously have an effect on audit delay of 60.2%. Auditors and companies can use this information to identify factors that cause audit delays.